MISSION AND TRANSMISSION - Manikkam, Thomas (Journal of Dharma, 1981)
Every religion worth its name emerging from a foundational experience of man embodies a certain message which implies some ultimate concern for man. The foundational character of such an experience, be it the mystic intuition of a Rsi from a cave of the Himalayas on the Reality of the Absolute, or the encounter of Moses with Yahweh on Mount Sinai, or the confrontation of Sri Buddha with duhkha (suffering) in the "Valley of Tears", or rather, the transformation of Jesus on Mount Tabor, or even the Pentecostal experience of his disciples in the Cinacle, or else the flash light that felled Saul from the horse-back on the road to Damascus, or the yogic vision of Arjuna about the Cosmic Form of Sri Krishna in the Dharma-kshetra of Kuru-k shiitra, all of them entail the urgency of a mission and a transmission: mission, because, the experience enshrines a message to be passed on to others who did not have the opportunity to have a taste of the pristine experience; transmission, because the message requires an appropriate process of transference for effective communication.